Replication and the Establishment of Scientific Truth - Iso-Ahola, Seppo E. (Frontiers in Psychology, 2020)
Abstract The idea of replication is based on the premise that there are permanent laws to be replicated and verified, and the scientific method is adequate for doing so. Scientific truth, however, is not absolute but relative to time and context, and the method used. Time and context are inextricably interwoven, in that time creates different contexts and contexts (e.g., Christmas Day vs. New Year’s Day) create different experiences of time, rendering psychological phenomena inherently variable. This means that internal and external conditions fluctuate and are different in a replication study vs. the original. Thus, a replication experiment is just another empirical investigation that has no special status in the establishment of scientific truth. It is not the final arbiter of whether or not something exists. In their pursuit of homogeneous external conditions, replications have ignored the homogeneity of internal conditions. There is not a single replication reported in the literature that would have shown participants’ feelings and thoughts—both conscious and nonconscious—to be identical to those of the original participants. Experimental instructions can create varying ratios of conscious over nonconscious processing from one study to another. Ironically, every replication is a failure at the fundamentals of human psychology. While patterns can be discovered, they are not permanent or unchangeable laws of human behavior to be proven by the pinpoint statistical verification through replication. As scientific knowledge in physics is temporary and incomplete, should it be any surprise that science can only provide “temporary winners” for psychological knowledge of human behavior?